Organisational readiness for change: implication for human resource development - Ogbodoakum, Nnamdi; Zainal Abiddin, Norhasni (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
Organisations are being challenged to adapt to the fast paced economic and social environments. Irrespective of the sector an organisation is operating (private, public, and non-profit), the cascading tide of globalisation, where economic factors are freely traded and exchanged have caused significant disruption in meeting various organisation objectives. Even though, the above organisations have different objectives, mission and vision, they want superior service delivery, which only a change ready organisation would provide. Change ready organisation starts with availability of empowered employees; who are competent and skilful in navigating the complex demand of change. It has been established that high rate of failure in organisational change implementation in most cases is estimated at about 70%. This ugly development is attributed to poor readiness of the organisation before those changes were introduced. A change ready organisation support rapid change implementation unlike incessant piecemeal perspective of change being introduced by managers as a way to reduce resistance. Such practices have produced more resistance, rejection and failures. Although, the role of human resource development in achieving sustained performance has been noted in many studies, very few have contextualised human resources development in the perspective of readiness for change, especially at the organisation level. Organisational readiness is the shared resolve of members to support change (commitment) and mutual understanding to implement change successfully (efficacy). Without shared resolve by the employees or staff to support and implement change, no meaningful organisational outcome will be achieved. When members of an organisation commit to change with common interest; improved organisational results are recorded. The core argument of Winner theory of organisational readiness for change is that change commitment and change efficacy is the function of change valance, situational factors, task demand and resource perception including broader contextual factors (organisational culture, organisational resources, policies and procedures and past experience). From the review, the authors found that HRD will play a critical and significant role in creating strong, and sustained organisational readiness for change by synchronizing HRD practices with organisation objectives as a strategic partner, which is valued and respected, otherwise HRD may be judged organisational cost which should be reduced.